Association of admission serum calcium level with left ventricular dysfunction in patients with acute coronary syndrome - Wang, Hong; Wang, Rongrong; Tian, Junping (Frontiers in Cardiovascular Medicine, 2022)
Background The relationship between serum calcium and left ventricular function in patients with acute coronary syndrome (ACS) has not been explored. Our aim was to investigate the correlation of admission serum calcium with left ventricular dysfunction in ACS patients. Methods In this cross-sectional study, 658 ACS patients who were admitted in the Department of Cardiovascular Disease from June 1st, 2019 to December 31st, 2019 were enrolled in the present study. Serum calcium and B-type natriuretic peptide (BNP) were measured at admission. Left ventricular ejection fraction (LVEF) was assessed using echocardiography. The correlation between admission serum calcium and left ventricular dysfunction was analyzed. Results When stratified by serum calcium quartiles calculated from all patients, patients with lower serum calcium quartile showed a markedly higher BNP and lower LVEF (P < 0.05). Patients with LVEF ≤ 50% showed a significantly lower serum calcium and higher BNP compared to those with LVEF> 50% (P < 0.05). Admission serum calcium was positively correlated with LVEF (P < 0.01) but negatively correlated with BNP (P < 0.01). Multivariate logistic regression analysis showed that lower serum calcium (adjusted OR: 0.720, 95% CI: 0.519–0.997, P = 0.048) was independently associated with BNP ≥ 300 pg/ml in ACS patients. Using LVEF as a dependent variable, no significant correlation between low serum calcium and left ventricular systolic dysfunction was found in ACS patients. Conclusions In patients with ACS, admission serum calcium was positively correlated with LVEF and negatively with BNP. Lower admission serum calcium was an independent risk factor for elevated BNP.